2016
DOI: 10.1016/s1470-2045(16)00078-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumour-associated macrophages with CCR2 inhibition in combination with FOLFIRINOX in patients with borderline resectable and locally advanced pancreatic cancer: a single-centre, open-label, dose-finding, non-randomised, phase 1b trial

Abstract: Background Pancreatic ductal adenocarcinoma utilizes the CCL2/CCR2 chemokine axis to facilitate recruitment of tumor associated macrophages to sculpt an immunosuppressive tumor microenvironment. This pathway has prognostic implications in pancreas cancer, and blockade of CCR2 restores anti-tumor immunity in pre-clinical models. This provided the rationale for a clinical study in pancreatic adenocarcinoma to determine the safety and recommended phase 2 oral dosage of the CCR2 inhibitor PF-04136309 in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
444
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 630 publications
(469 citation statements)
references
References 31 publications
6
444
2
Order By: Relevance
“…Inhibiting the CCR2-CCL2 axis modulates both T and non-T cell immune mechanisms, potentially leading to enhanced response in combination with cytotoxic chemotherapy (74). Intriguingly, it appears that myeloid cell depletion is crucial to inducing durable anti-tumor immune responses (73,74,77).…”
Section: Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting the CCR2-CCL2 axis modulates both T and non-T cell immune mechanisms, potentially leading to enhanced response in combination with cytotoxic chemotherapy (74). Intriguingly, it appears that myeloid cell depletion is crucial to inducing durable anti-tumor immune responses (73,74,77).…”
Section: Immunotherapymentioning
confidence: 99%
“…Inhibiting the CCR2-CCL2 axis modulates both T and non-T cell immune mechanisms, potentially leading to enhanced response in combination with cytotoxic chemotherapy (74). Intriguingly, it appears that myeloid cell depletion is crucial to inducing durable anti-tumor immune responses (73,74,77). With increasing immunotherapies becoming available and entering clinical trials, there is an urgent need to identify biomarkers of response to stratify patients to effective immunotherapy combinations at appropriate time-points in the tumor life-span.…”
Section: Immunotherapymentioning
confidence: 99%
“…In a phase 1b trial of borderline resectable and locally advanced PDAC, the small molecule CCR2 inhibitor PF-04136309, in combination with FOLFIRINOX, was safe and tolerable, and displayed an objective tumor response of 49% (16/33 patients), compared to zero of five patients treated with FOLFIRINOX alone. As expected, the addition of PF-04136309 resulted in a re-distribution of CCR2-positive monocytes from the peripheral blood to the bone marrow compartment (the opposite of that seen with FOLFIRINOX alone) and an approximate 4-fold decrease in the number of tumor-associated macrophages (TAM), a 2-fold increase in the number of CD4 + and CD8 + T cells, and nearly a 6-fold decrease in the number of Tregs in tumors compared to FOLFIRINOX alone (48). This work lays the foundation for further investigation into CCR2 modulation in pancreatic cancer.…”
Section: Ccr2 Modulation In Pdacmentioning
confidence: 98%
“…The CCL2‐CCR2 axis is important for the recruitment of tumor‐associated macrophages in pancreatic ductal adenocarcinoma and leads to an immunosuppressive tumor microenvironment. Further preclinical models also demonstrated that blockade of CCR2 can lead to recovery of antitumor immunity 78. The orally bioavailable CCR2 inhibitor PF‐4136309 ( 34 , Pfizer, Figure 19) was investigated in a phase I study in combination with the FOLFIRINOX chemotherapy regimen in patients with borderline resectable and locally advanced pancreatic adenocarcinoma.…”
Section: Phoenix From the Ashes: Chemokine Receptor Antagonistsmentioning
confidence: 99%
“…The orally bioavailable CCR2 inhibitor PF‐4136309 ( 34 , Pfizer, Figure 19) was investigated in a phase I study in combination with the FOLFIRINOX chemotherapy regimen in patients with borderline resectable and locally advanced pancreatic adenocarcinoma. The compound was reported to be safe, and an improvement in tumor response could be observed 78, 79. PF‐413609 is also being tested in a phase Ib/II study in combination with Gemcitabine and Nab‐Paclitaxel in first‐line metastatic pancreatic patients 80.…”
Section: Phoenix From the Ashes: Chemokine Receptor Antagonistsmentioning
confidence: 99%